P. Ramlee one stop centre: collaboration with Tempatan Fest / Mohamad Aliff Naim Arifin - Arifin, Mohamad Aliff Naim (Faculty of Art and Design, 2020)
The new generation has changed and the P. Ramlee era has been overlooked, with the aid of this P. Ramlee graphic design campaign, it would introduce a new figure of P. Ramlee and familiarize the generation once more with forgotten P. Ramlee era.